Gender disparities in eHealth literacy among Chinese university students and their decomposition - Yuyao Song; Yusupujiang Tuersun; Qingping Zhou; Wenyu Wang; Yao Yu; Chenxi Wang; Hanyue Liu; Yao Wu; Yuying Xie; Zhenning Liang; Yi Qian (Frontiers in Public Health, 2026)
Background As a high-frequency user group of the internet, university students’ eHealth literacy not only affects their own health but also has a radiating effect on the health literacy of the entire population. Gender disparities may lead to an imbalance in eHealth literacy among university students, thereby affecting their health status. Understanding these disparities is important from a public health perspective for designing equitable digital health interventions. Methods The eHealth Literacy Scale was used to assess the eHealth literacy levels of 7,230 university students from various institutions and majors across 10 regions. Chi-square tests and binary logistic regression were employed to analyze factors associated with gender disparities in eHealth literacy, and the Fairlie decomposition model was used to quantify the contribution of each factor. Results The average eHealth literacy score of the sampled Chinese university students was 29.22 ± 6.68. Of the 7,230 students, 4,135 (57.2%) scored below the 32-point eHEALS cut-off. Regarding gender, female students had a significantly higher rate of inadequate eHealth literacy (2,847/4,820, 59.07%) compared with male students (1,288/2,410, 53.44%; p < 0.001). The Fairlie decomposition analysis showed that 55.0% of the disparity in eHealth literacy was attributable to unmeasured variables, differences in coefficients, measurement error, or residual confounding, while 45.0% resulted from observed factors. Among these, depressive symptoms (PHQ-9) were the largest contributing factor (28.57%), followed by type of household (14.29%), monthly per capita household income (10.71%), and exercise level (−3.57%). Conclusion Significant gender disparities exist in eHealth literacy among Chinese university students, with male students showing higher levels. This disparity is associated with mental health status, socioeconomic status, and lifestyle behaviors. This study proposes several potential strategies including fostering a gender-equal atmosphere, optimizing digital resource allocation, and strengthening campus mental health services that may help to narrow the gap.